1992
DOI: 10.1021/jm00094a002
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of the .delta. opioid receptor selective cyclic peptide [cyclic][2-D-penicillamine,5-D-penicillamine]-enkephalin: 2',6'-dimethyltyrosine and Gly3-Phe4 amide bond isostere substitutions

Abstract: In order to develop systemically-active opioid peptides, the delta-selective, opioid pentapeptide [D-Pen2,D-Pen5]-enkephalin (DPDPE) was modified by esterification and by substitution of 2',6'-dimethyltyrosine for tyrosine to yield 4. Compound 4 was on the order of 8- and 800-fold more active than DPDPE in both delta and mu opioid radioligand binding assays, respectively, in rat neural membrane suspensions. Compound 4 was considerably more potent than DPDPE at inhibiting contractions of electrically-stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…High‐resolution FAB + and CI + mass spectra [high‐resolution mass spectrometry (HRMS)] were obtained on a JEOL MStation MS‐700. 1 H and 13 C NMR data for the compounds 13 – 15 and 5 were identical to those described in the literature.…”
Section: Methodssupporting
confidence: 56%
“…High‐resolution FAB + and CI + mass spectra [high‐resolution mass spectrometry (HRMS)] were obtained on a JEOL MStation MS‐700. 1 H and 13 C NMR data for the compounds 13 – 15 and 5 were identical to those described in the literature.…”
Section: Methodssupporting
confidence: 56%
“…The development of a unique analogue of Tyr, achieved through methylation of the 2′ and 6′ positions of the tyramine ring to yield Dmt49 paved the way for realizing increased bioactivities in small opioid dipeptides. Whereas some substitutions of Dmt into [2‐ D ‐penicillamine, 5‐ D ‐penicillamine]‐enkephalin (DPDPE) and Dmt‐ N ‐(3‐phenylpropyl)‐ D ‐alaninamide did not yield dramatic results,50–53 the incorporation of Dmt into H–Tyr–Tic–OH increased δ‐receptor affinity 8500‐fold 54. This finding revolutionized the opioid field by clearly demonstrating that a single amino acid residue can have monumental effects on the opioid receptor affinity and bioactivity and firmly established the Dmt–Tic pharmacophore (Figure 1) as a new template for opioid ligand design 54, 55…”
Section: Introductionmentioning
confidence: 99%
“…Later alterations in opioid structure, in particular the substitution of the N-terminal residue Tyr by Dmt (Chandrakumar et al, 1992;Hansen et al, 1992;Pitzele et al, 1994;Guerrini et al, 1996;Salvadori et al, 1997;Sasaki et al, 1999;Schiller et al, 2000;Bryant et al, 2003) and dimerization of Dmt through alkyldiamine , led to increases in the binding to opioid receptors and bioactivities in vitro and in vivo (Bryant et al, 2003). This study provided evidence that a pyrazinone ring connecting to two symmetric Dmt N termini by alkyl chains might serve a dual role in opioid peptides as both message and address domains.…”
Section: Discussionmentioning
confidence: 75%
“…Message and address domains of opioid peptides represent distinct starting points for the design and development of novel opioid mimetics. For example, studies on opioid peptides showed that the substitution of the N-terminal tyrosine by 2Ј,6Ј-dimethyl-L-tyrosine (Dmt) dramatically increased receptor affinity in numerous peptides and enhanced their antinociceptive effect (Chandrakumar et al, 1992;Hansen et al, 1992;Pitzele et al, 1994;Guerrini et al, 1996;Sasaki et al, 1999;Schiller et al, 2000;Bryant et al, 2003). Moreover, Dmt played a key role in the formation of the Dmt-Tic pharmacophore family of potent ␦-opioid receptor antagonists (Salvadori et al, 1997;Bryant et al, 1998, which were transformed into potent ␦-opioid receptor agonists by subtle changes in the C-terminal link to a third aromatic nucleus (Balboni et al, 2002).…”
mentioning
confidence: 99%